2015
DOI: 10.1144/qjegh2014-078
|View full text |Cite
|
Sign up to set email alerts
|

Critical rainfall thresholds for debris flows in Sanyanyu, Zhouqu County, Gansu Province, China

Abstract: Critical rainfall thresholds can be the key to ensuring effective debris-flow forecasting. They are significant for the study of the trigger mechanisms of debris flows, for the forecast of the characteristics of future events, and for the development of engineering guidance for mitigation. Using a hydrological approach, we first calculated the flood peak discharge at different frequencies and then the corresponding rainfall thresholds for the initiation of different scales of debris flows in Zhouqu County, Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 10 publications
0
18
0
2
Order By: Relevance
“…The topography is characterized by rugged mountains and deeply incised valleys with elevations ranging from 1200 m to more than 4000 m a.s.l. which has a strong influence on local climate: high relative relief causes rainfall to concentrate in the high-altitude areas, with much less precipitation in the valleys, resulting in the so-called dry and hot valleys system in this region as defined in Yu et al (2015).…”
Section: Study Areamentioning
confidence: 99%
“…The topography is characterized by rugged mountains and deeply incised valleys with elevations ranging from 1200 m to more than 4000 m a.s.l. which has a strong influence on local climate: high relative relief causes rainfall to concentrate in the high-altitude areas, with much less precipitation in the valleys, resulting in the so-called dry and hot valleys system in this region as defined in Yu et al (2015).…”
Section: Study Areamentioning
confidence: 99%
“…Several countermeasures against this type of event happening again in the future have been presented on the basis of its factors of influence, characteristics, and trends (Hu et al 2010;Yan et al 2010;Liu et al 2011). However, under the same conditions, the likelihood of fatal flows occurring when it rains heavily remains high (Yu et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…They posed high risk to human lives. Since 12 May 2008, large numbers of debris flow events have occurred in the Wenchuan seismic area and have caused thousands of deaths (Xie et al, 2009;Tang and Tie, 2009;Cui et al, 2010;Xu, 2010;Yu et al, 2010). The debris flow event that took place on 7 August 2010 in Zhouqu led to more than one thousand people losing their lives (Yu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Since 12 May 2008, large numbers of debris flow events have occurred in the Wenchuan seismic area and have caused thousands of deaths (Xie et al, 2009;Tang and Tie, 2009;Cui et al, 2010;Xu, 2010;Yu et al, 2010). The debris flow event that took place on 7 August 2010 in Zhouqu led to more than one thousand people losing their lives (Yu et al, 2010). Studies on the Chi-Chi seismic area have shown that the threshold of accumulated rainfall for triggering debris flow would drop significantly after a large earthquake (Chen, 2008;Liu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%